Simulation of a surface mount technology (SMT) system - Tan, Lai Soon. (2008)
Surrounded with competition from neighbouring countries and increasing costs such as labour and overheads, the manufacturing companies today are facing a higher degree of pressure in order to survive in industry. Manufacturing firms must constantly reduce their operating costs and optimise the process to achieve the objective of producing the best quality products at the lowest possible cost. Therefore, decision making becomes critical. In order to make a rapid and realistic decision, tools are needed to facilitate the analysis process.